Modular session types for objects - Gay, Simon J. (2017)
We thank Jonathan Aldrich and Luis Caires for helpful discussions. Gay was partially supported by the UK EPSRC (EP/E065708/1 "Engineering Foundations of Web Services", EP/F037368/1 "Behavioural Types for Object-Oriented Languages", EP/K034413/1 "From Data Types to Session Types: A Basis for Concurrency and Distribution" and EP/L00058X/1 "Exploiting Parallelism through Type Transformations for Hybrid Manycore Systems"). He thanks the University of Glasgow for the sabbatical leave during which part of this research was done. Gay and Ravara were partially supported by the Security and Quantum Information Group at Instituto de Telecomunicacoes, Portugal. Vasconcelos was partially supported by the Large-Scale Informatics Systems Laboratory, Portugal. Ravara was partially supported the Portuguese Fundacao para a Ciencia e a Tecnologia FCT (SFRH/BSAB/757/2007), and by the UK EPSRC (EP/F037368/1). Gesbert was supported by the UK EPSRC (EP/E065708/1) and by the French ANR (project ANR-08-EMER-004 "CODEX"). All of the authors have received support from COST Action IC1201 "Behavioural Types for Reliable Large-Scale Software Systems".